SOSIALISASI KONSEP PARIWISATA BERKELANJUTAN DALAM PENGELOLAAN OBJEK WISATA PANTAI YEH GANGGA KABUPATEN TABANAN - PUTRA, AGUS MURIAWAN (Buletin Udayana Mengabdi; Vol 8 No 1 (2009): Volume 8 No.1 – April 2009, 2012)
ABSTRACT The Bali Sustainable Development Project suggested that the sustainable development concept for Bali should reflect a balance between economy, environment and culture. This should, therefore incorporate the need for continuity of natural resources and production, the need for continuity of culture and the balances within culture, and development as an "optimum process" that can enhance quality of life. The Bali Sustainable Development Project has developed seven special criteria : (1) ecological integrity (2) efficiency (3) equity: (4)cultural integrity (5) community (6) to integrate key factors, such as economy, environment, and agriculture and tourism; and (7) to enhance the capabilities of its institutions at all levels to address all needs and improve quality of life. Yeh Gangga Beach, the tourism destination in Tabanan was given a presentation from the Tourism Program of Udayana University about “Tourism Sustainable in Yeh Gangga Beach”. Responses from the people were very enthusiastics and positif because according factual issues in that destination, the people want to participate directly to increase the profit from that tourism activities.